2015
DOI: 10.1002/cmdc.201500267
|View full text |Cite
|
Sign up to set email alerts
|

One Question, Multiple Answers: Biochemical and Biophysical Screening Methods Retrieve Deviating Fragment Hit Lists

Abstract: Fragment-based lead discovery is gaining momentum in drug development. Typically, a hierarchical cascade of several screening techniques is consulted to identify fragment hits which are then analyzed by crystallography. Because crystal structures with bound fragments are essential for the subsequent hit-to-lead-to-drug optimization, the screening process should distinguish reliably between binders and non-binders. We therefore investigated whether different screening methods would reveal similar collections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(109 citation statements)
references
References 49 publications
3
101
0
5
Order By: Relevance
“…35 The highest hit rate was found for biochemical screening (17%) followed by NMR (11%) and thermal shift assay (8%). It is important to note, however, that the authors neither The different assays were performed under similar conditions including the buffers.…”
Section: Methodsmentioning
confidence: 98%
“…35 The highest hit rate was found for biochemical screening (17%) followed by NMR (11%) and thermal shift assay (8%). It is important to note, however, that the authors neither The different assays were performed under similar conditions including the buffers.…”
Section: Methodsmentioning
confidence: 98%
“…Dies schränkt den Einsatz von biochemischen Aktivitätsassays,d ie auf spektroskopischen Methoden wie Fluoreszenz-oder UV/Vis-Spektroskopie beruhen, deutlich ein. [24] Biophysikalische Methoden wie die Biolayer-Interferometrie sind bezüglich Assayinterferenzen weniger stçranfällig und daher für fragmentbasiertes Screening besser geeignet. [25] Um die Eignung unserer SirReal-Sonde in Kombination mit der Biolayer-Interferometrie für fragmentbasierte Screeningansätze zu prüfen, testeten wir Fragmente von SirReal2 (2) [26] zu identifizieren und genomweite Bindungsprofile für Sirt2 durch Chem-seq [27] zu erstellen.…”
unclassified
“…2628 The use of MST is increasingly being reported in fragment-based drug discovery, 23,24,3033 including kinases such as p38α 30 and MEK1, 31 and the bromodomain BRD9. 32 In both the MEK1 study by Sanofi in collaboration with NanoTemper and the BRD9 study by Boehringer Ingelheim, MST was used to confirm the binding of fragments identified by SPR and DSF, as well as to identify additional hits not detected by the other techniques.…”
Section: Microscale Thermophoresismentioning
confidence: 99%